Skin flap shift is associated with postoperative complications after cranioplasty: a retrospective cohort study - Liu, Shangshuo; Dang, Ronglun; Li, Yida; Ma, Liyuan; Zhou, Wenke (Frontiers in Neurology, 2025)
BackgroundThe incidence of postoperative complications following cranioplasty (CP) procedures remains relatively high, which has a significant impact on patient prognosis. While current research on predictive factors for complications has focused primarily on patient demographics, the timing of surgery and material selection, the association between skin flap shift and complications has yet to be systematically evaluated.ObjectiveTo investigate the correlation between skin flap shift and postoperative complications following CP.MethodsA cohort of patients undergoing CP was enrolled and categorized into postoperative complication and no-complication groups. First, we conducted a univariate analysis on the following variables: age; gender; medical history; and surgical variables. Variables with a p-value of ≤0.2 in the univariate analysis were included in the multivariate logistic regression analysis. For the continuous variables, ROC curves were used to determine the optimal cut-off values for predicting complications. These values were then converted into binary variables for the multivariate analysis.ResultsUnivariate analysis demonstrated that the differences in the materials utilized for repair, intraoperative blood loss, and skin flap shift between the two groups were statistically significant. The optimal cutoff values for intraoperative blood loss and skin flap shift, as determined by ROC curve analysis, were identified as 175 mL and 13.55 mm, respectively. Multivariate logistic regression analysis identified skin flap shift to be independently associated with postoperative complications after CP. (OR: 3.239, 95% CI: [1.450–7.237], p = 0.004). The area under the curve for predicting postoperative complications based on skin flap shift was 0.719 (95%CI: 0.646–0.797).ConclusionSkin flap shift was independently associated with postoperative complications following CP surgery. Patients with flap displacements exceeding 13.55 mm are at an increased risk of experiencing such complications.